Kualitas Pelayanan Kesehatan Di Puskesmas Pembantu (Pustu) Desa Lebang Kecamatan Cendana Kabupaten Enrekang - Hamdan Hamdan; Musliha Karim; Samsir Rahim (Department of Public Administration, Muhammadiyah University of Makassar, 2017)
The objectives of this research were to describe and to explain about the quality of health services at auxiliary community health centers in Lebang village of Cendana subdistrict in Enrekang regency. The research method of this research was quantitative descriptive that used to explain about the quality of auxiliary community health centers.The respondent were 68 people which were chosen by using incidental sampling. There were some steps in procedures of collecting data. They were question, observation, and interview. The collected data were analyzed by using frequency table. The result of the research showed that the quality of health services at auxiliary community health centers was already good and qualified. These results were based on the recapitulations of each indicators as follows tangible, reliability, competence, and responsiveness where all the mean results were in a good and qualified category.Keywords: quality, healthy service Penelitian ini bertujuan untuk menggambarkan dan menjelaskan kualitas pelayanan kesehatan di Puskesmas pembantu (PUSTU) Desa Lebang Kecamatan Cendana Kabupaten Enrekang. Jenis penelitian adalah deskriptif kuantitatif yang menjelaskan mengenai kualitas pelayanan kesehatan di PUSTU. Responden sebanyak 68 orang yang dipilih secara sampling insidental.Teknik pengumpulan data yaitu kuesioner, observasi, dan wawancara. Data tersebut dianalisis secara deskriptif kuantitatif menggunakan tabel frekuensi.Hasil penelitian menunjukkan bahwa kualitas pelayanan kesehatan sudah baik dan berkualitas.Hal ini berdasarkan hasil rekapitulasi dari tiap-tiap indikator yaitu bukti fisik (tangible), keandalan (reliability), kompetensi (competence), dan responsivitas (responsiveness) dengan hasil rata-rata persentase berada pada kategori baik dan berkualitas.Katakunci: kualitas, pelayanan kesehatan.